2004
DOI: 10.1080/15459620490467792
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Service Lives of Organic Vapor Cartridges II: A Single Vapor at All Humidities

Abstract: A widely used equation model for estimating service lives of organic vapor air-purifying respirator cartridges has been updated with more recent research results. It has been expanded to account for effects of high relative humidities. Adsorption capacity competition between water vapor and organic vapor is largely explained by mutual exclusion of adsorption volume of the activated carbon. The Dubinin/Radushkevich equation is used to describe the adsorption isotherms of both water and organic vapors. Effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Following this conversion, we applied the estimation model of the breakthrough time by Wood et al 21) . In this model, the service lives of cartridges or activated carbon beds for organic vapors are estimated by extension 21,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] 1) where: t b = breakthrough time (min), W e = adsorption capacity of carbon (g/g-carbon), W = carbon bed weight (g), C 0 = challenge vapor concentration (g/cm 3 ), C = breakthrough concentration (g/cm 3 ), Q = airflow rate (cm 3 /min), ρ B = bulk density of carbon (g/cm 3 ), k v = adsorption rate coefficient (min -1 ). In the estimation, a single vapor is assumed to be the adsorbate, and the Dubinin-Radushkevich (D-R) equation (Equation 2) 44,45) is used to calculate the value of W e for individual organic vapors: (2) where: W 0 = micropore volume or adsorption space (cm 3 /g-carbon), d L = liquid density of adsorbate (g/cm 3 ), R = ideal gas constant (8.315 kJ · K -1 /mol), T = temperature (K), b OV = affinity coefficient of organic vapor (dimensionless parameter), E 0 = adsorption energy of a reference adsorbate (kJ/ mol), p sat = bulk liquid saturation vapor pressure at the temperature (kPa), p = pressure of vapor (kPa).…”
Section: Calculation Of the Breakthrough Time By Extension Of The Whementioning
confidence: 99%
See 1 more Smart Citation
“…Following this conversion, we applied the estimation model of the breakthrough time by Wood et al 21) . In this model, the service lives of cartridges or activated carbon beds for organic vapors are estimated by extension 21,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] 1) where: t b = breakthrough time (min), W e = adsorption capacity of carbon (g/g-carbon), W = carbon bed weight (g), C 0 = challenge vapor concentration (g/cm 3 ), C = breakthrough concentration (g/cm 3 ), Q = airflow rate (cm 3 /min), ρ B = bulk density of carbon (g/cm 3 ), k v = adsorption rate coefficient (min -1 ). In the estimation, a single vapor is assumed to be the adsorbate, and the Dubinin-Radushkevich (D-R) equation (Equation 2) 44,45) is used to calculate the value of W e for individual organic vapors: (2) where: W 0 = micropore volume or adsorption space (cm 3 /g-carbon), d L = liquid density of adsorbate (g/cm 3 ), R = ideal gas constant (8.315 kJ · K -1 /mol), T = temperature (K), b OV = affinity coefficient of organic vapor (dimensionless parameter), E 0 = adsorption energy of a reference adsorbate (kJ/ mol), p sat = bulk liquid saturation vapor pressure at the temperature (kPa), p = pressure of vapor (kPa).…”
Section: Calculation Of the Breakthrough Time By Extension Of The Whementioning
confidence: 99%
“…Among these influencing factors, moisture content has been the focus of many quantitative researches, and there are many reports [6][7][8][9][10][11][12][13][14][15][16][17][18][19] regarding its effect on gas filters or experimental packed beds of activated carbon at room temperature (approximately at 293-298 K). Further, Wood et al have reported the effective estimation of the breakthrough time of activated carbon beds for organic vapors 20,21) which covers the effect of all levels of relative humidities by extension of the Wheeler-Jonas breakthrough time equation [22][23][24] modified by Yoon et al 25,26) . These researches revealed that the adsorption capacity of acti-vated carbon for organic vapors is reduced by the moisture content of the carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, Wood et al have reported kinetics studies of the adsorption rate and the capacity of the activated carbon bed for organic vapors [15][16][17][18][19] . They have also reported estimations of the adsorption capacities of organic vapors of activated carbon beds 19) considering the effect of all levels of relative humidity by extension of the Wheeler-Jonas breakthrough time equation 18,20) .…”
Section: Introductionmentioning
confidence: 99%
“…They have also reported estimations of the adsorption capacities of organic vapors of activated carbon beds 19) considering the effect of all levels of relative humidity by extension of the Wheeler-Jonas breakthrough time equation 18,20) . In their report 19) , they used many previous measurement data by other researchers for model testing, and their calculations are consistent with the data at high concentrations of organic vapors, greater than or equal to 1,000 ppm. However, the results of their calculations are inconsistent with the experimental data at low concentrations below 100 ppm, and long breakthrough time range in each figure.…”
Section: Introductionmentioning
confidence: 99%
“…The most common model used by OSHA and some manufacturers is the Wood math model (12) for estimating the service life of single (11) and multiple organic vapour cartridges (12) at different humidity levels.…”
mentioning
confidence: 99%